Comparison of “Huaxi-1” or “histidine-tryptophan-ketoglutarate” cardioplegia in an animal model - Yu, Xiang; Xiong, Wen; Zhang, Jie; Lin, Jing; Wang, Bo; Huang, Hong; Du, Lei; Xiong, Jiyue (Frontiers in Cardiovascular Medicine, 2024)
BACKGROUNDː Using a pig model of cardiopulmonary bypass, we compared outcomes after cardioplegia either with our in-house "Huaxi-1" solution containing natural blood and crystalloid or with the entirely crystalloid, commercially available "histidine-tryptophanketoglutarate" solution.METHODSː Cardiopulmonary bypass was established in 12 healthy male pigs, who were randomized to receive a single dose of either Huaxi-1 or entirely crystalloid. All animals were then subjected to whole-heart ischemia for 90 min, followed by 2 h of reperfusion, after which myocardial injury was assessed in terms of cardiac function, myocardial pathology and levels of biomarkers in plasma, while levels of high-energy phosphate in myocardium were assayed using liquid chromatography.RESULTSː Animals given Huaxi-1 cardioplegia required significantly less time to be weaned off bypass, they received significantly lower doses of norepinephrine, and they showed significantly higher levels (mean ± SD) of adenosine triphosphate (14 ± 4 vs 8 ± 2 g/mg, P = 0.005), adenosine diphosphate (16 ± 2 vs 13 ± 2 g/mg, P = 0.046), and total adenine nucleotide (37 ± 4 vs 30 ± 3 g/mg, P = 0.006) in myocardium after 2 h of reperfusion. They also showed less severe bleeding, edema and injury to mitochondria and myofibers in myocardium. The two groups did not differ significantly in doses of inotropic drugs received, cardiac output or levels of biomarkers in plasma.CONCLUSIONSː In this animal model of healthy hearts subjected to 90 min of ischemia, Huaxi-1 cardioplegia may be superior to entirely crystalloid cardioplegia for promoting energy generation and attenuating ischemia/reperfusion injury in myocardium.